Two dogs - Falconer, Ian, 1959- (New York : HarperCollins Publishers, 2022)
Dachshund brothers Perry and Augie are home alone and desperately want to get outside and have a good time. Augie is the cautious one, the worrier; Perry is pure joy and excitement. When they finally manage to open the back door, mischievous adventures begin! Soon they're diving into the swimming pool, digging an enormous hole, and more! Will all return to normal before their owners come home?
K-3
1.6
Keywords: Dachshunds -- Fiction; Dogs -- Fiction; Brothers -- Fiction; Animal fiction; Humorous stories